MEDICAL RECORDS VOCABULARIES: LEARNING STRATEGIES UNDERSTANDING - Santy Christinawati; Wahyu Trimastuti (Jurnal Infokes, 2021)
Vocabulary is one of the supporting factors in the success of language learning. Developing the ability to communicate in English either in spoken or written form includes listening, speaking, reading, and writing. One of the most important aspects of language learning is vocabulary. Understanding vocabulary is considered important in the process of language learning or the development of a person's ability in a controlled language. Not all vocabularies have the same meaning. All understanding will depend on the context.